Praanggapan Pada Tuturan Neneng Garut: Kajian Pragmatik dalam Stand Up Comedy Academy (SUCA 3) - Prapti Wigati Purwaningrum (Wanastra: Jurnal Bahasa dan Sastra, 2019)
The aim of this study is to examine the presuppositions of Neneng Garut's utterances through pragmatic studies. This is a qualitative study with content analysis method because this study prioritizes the content approach of the speech. The data source of this research is Neneng Garut's utterances which contains presuppositions and implicature in Stand Up Comedy Academy (SUCA 3). Data provision of this analysis is done by using simak method that is applied through note-taking techniques. The results of this study indicate that Neneng Garut would like to convey that at present more and more cases of corruption have occurred and are increasingly difficult to stop it. This is said through the puncline and if we ask Indonesia for corruption free, it is very difficult, especially when we ask Radit to marry, it is more difficult. In addition, in this study also found some presuppositions in her utterances such as, presuppositions about the difficulty and limited transportation in remote region of Garut, the lack of entertainment, trust in mysticism that is still very thick, and a way of thinking in society. In addition, through pragmatic, presupposition, and understanding the implicit meanings, the writer hopes that the results of this paper will be able to contribute ideas to the reading community about the importance of hearing and understanding the speech of the partners in a society that has lately faded.